Making Residents Part of the Safety Culture: Improving Error Reporting and Reducing Harms. Issue 5 (August 2021) - Fox, Michael D.; Bump, Gregory M.; Butler, Gabriella A.; Chen, Ling-Wan; Buchert, Andrew R.
Abstract : Objectives: Reporting medical errors is a focus of the patient safety movement. As frontline physicians, residents are optimally positioned to recognize errors and flaws in systems of care. Previous work highlights the difficulty of engaging residents in identification and/or reduction of medical errors and in integrating these trainees into their institutions' cultures of safety. Methods: The authors describe the implementation of a longitudinal, discipline-based, multifaceted curriculum to enhance the reporting of errors by pediatric residents at Children's Hospital of Pittsburgh of University of Pittsburgh Medical Center. The key elements of this curriculum included providing the necessary education to identify medical errors with an emphasis on systems-based causes, modeling of error reporting by faculty, and integrating error reporting and discussion into the residents' daily activities. The authors tracked monthly error reporting rates by residents and other health care professionals, in addition to serious harm event rates at the institution. Results: The interventions resulted in significant increases in error reports filed by residents, from 3.6 to 37.8 per month over 4 years ( P < 0.0001). This increase in resident error reporting correlated with a decline in serious harm events, from 15.0 to 8.1 per month over 4 years ( P = 0.01). Conclusions: Integrating patient safety into the everyday resident responsibilities encourages frequent reporting and discussion of medical errors and leads to improvements in patient care. Multiple simultaneous interventions are essential to making residents part of the safety culture of their training hospitals.